2017
DOI: 10.1177/1757913917703419
|View full text |Cite
|
Sign up to set email alerts
|

What can the food and drink industry do to help achieve the 5% free sugars goal?

Abstract: General rightsThis document is made available in accordance with publisher policies. Please cite only the published version using the reference above. Full terms of use are available: http://www.bristol.ac.uk/pure/about/ebr-terms 1 What can the food and drink industry do to help achieve the 5% free sugars goal? AcknowledgementsThis work was funded by an unconditional grant from Sugar Nutrition UK. We followed guidelines for scientific integrity that ensured the funders had no role in the workshop or preparati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 20 publications
2
19
0
Order By: Relevance
“…A paper summarising the outcome of an expert panel workshop concluded that the strategies with greatest potential to help consumers reduce their free sugars intake (taking into account feasibility, cost, effectiveness and likely consumer acceptability) are wider use of intense sweeteners and a gradual reduction in portion sizes of food and drinks high in sugars but relatively low in micronutrients (Gibson et al 2017).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…A paper summarising the outcome of an expert panel workshop concluded that the strategies with greatest potential to help consumers reduce their free sugars intake (taking into account feasibility, cost, effectiveness and likely consumer acceptability) are wider use of intense sweeteners and a gradual reduction in portion sizes of food and drinks high in sugars but relatively low in micronutrients (Gibson et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In their recent paper, Gibson and colleagues propose a combination of polyols for sweetness and dietary fibre for bulk (Gibson et al . ).…”
mentioning
confidence: 97%
See 2 more Smart Citations
“…A review on this dietary topic concluded that reducing the current intake level is feasible, although not to 5% in the near future. 9 The multiple strategies required include use of alternative sweeteners, smaller portion size and clearer guidance. Pharmacists have a role in promoting less obesogenic diets, as do slimming organisations: Healthy Living Pharmacies (HLPs) in Durham achieved impressive results through an integrated approach.…”
mentioning
confidence: 99%